New perspectives on faking in personality assessment - Ziegler, Matthias, 1978-; MacCann, Carolyn; Roberts, Richard D. (New York ; Oxford : Oxford University Press, 2012)
Contributors consider what it means to "fake" a personality assessment, why and how people try to obtain particular scores on personality tests, and what types of tests people can successfully manipulate. The authors present and discuss the usefulness of a range of traditional and cutting-edge methods for detecting and controlling the practice of faking.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Personality assessment